Bevacizumab for Hearing Preservation in Neurofibromatosis Type 2: Emphasis on Patient‐Reported Outcomes and Toxicities. (30th October 2018) - Sverak, Pavlina; Adams, Meredith E.; Haines, Stephen J.; Levine, Samuel C.; Nascene, David; Sommer, Katherine; Dusenbery, Kathryn; Huang, Tina C.; Moertel, Christopher
Abstract : Objective: Bevacizumab for hearing preservation in patients with neurofibromatosis type 2 (NF2) is an emerging practice. We set out to characterize the effectiveness and toxicity of bevacizumab in our patient group. Study Design: Case series with chart review. Setting: Tertiary referral center. Subjects and Methods: Seventeen consecutive patients with NF2 received bevacizumab treatment for vestibular schwannomas, including 2 patients treated to maintain cochlear implant performance. Volumetric analysis of serial magnetic resonance imaging scans was used to evaluate radiographic response, and hearing response was evaluated with serial audiograms. Patient‐reported outcomes were also assessed, including subjective hearing improvement, changes in tinnitus, vertigo, headaches, ear pain, and improvement in ability to communicate via telephone. Results: A positive radiographic response occurred in 8 of 17 (47%) patients and the median tumor volume change was a tumor decrease of 19%. A positive hearing response was recorded in 5 of 9 (56%) patients. Two patients had a word recognition score improvement over 40%. There was an approximately 40% improvement in patient‐reported outcomes. Primary toxicities included hypertension, proteinuria, dysgeusia, and amenorrhea. Conclusion: Bevacizumab treatment was followed by hearing improvement in 56% of patients, while decreased tumor volume was noted in 47%. These outcomes agree favorably with prior reported series. There were significant improvements in patient‐reported outcomes that have not been described previously.